2011
DOI: 10.1021/ol200601e
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Free Direct Arylations of Indoles and Pyrroles with Diaryliodonium Salts

Abstract: Direct arylations of indoles and pyrroles with differently substituted diaryliodonium salts were shown to efficiently proceed in the absence of metal catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
96
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(105 citation statements)
references
References 48 publications
7
96
0
1
Order By: Relevance
“…10 A potentially more sustainable approach is the direct arylation of aromatic rings employing an aryl radical species generated in-situ. 11,12 Aryl radical species 1 can be obtained from the corresponding arylboronic acids 2, [13][14][15][16] arylhalides 3, 17 aryldiazonium salts 4 [18][19][20][21] and diaryliodonium salts 5 [22][23][24] (Figure 1). Addition of the aryl radical to a second aryl species followed by oxidation / rearomatisation then Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…10 A potentially more sustainable approach is the direct arylation of aromatic rings employing an aryl radical species generated in-situ. 11,12 Aryl radical species 1 can be obtained from the corresponding arylboronic acids 2, [13][14][15][16] arylhalides 3, 17 aryldiazonium salts 4 [18][19][20][21] and diaryliodonium salts 5 [22][23][24] (Figure 1). Addition of the aryl radical to a second aryl species followed by oxidation / rearomatisation then Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Supporting information for this article is given via a link at the end of the document. processes are rare, they have been accomplished through the use of hypervalent iodine reagents, [19][20][21] diazonium salts, [22] or by means of electrochemistry. [23][24][25] Our group has a longstanding interest in the reaction of indoles and related heterocycles.…”
mentioning
confidence: 99%
“…In 2011, C-H arylations of indoles and pyrroles with aryliodonium salts as coupling partner were reported by Sanford [65] and Ackermann [66]. As mentioned earlier, previous studies from the Sanford group [52] had shown that palladium catalysts can assist the direct arylation of indoles using aryliodonium salts; more recent studies attempted the coupling of aryliodonium salts with more sterically hindered heteroarenes such as 2,5-disubstituted pyrroles.…”
Section: Indoles and Pyrroles -Electron-rich Heteroarenesmentioning
confidence: 98%